Influencing elements to implement corporate governance in SMEs: a study with Financial Excellence Limited - Hosen, Md. Sazzad (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.